EVALUATION OF LOCAL GOVERNMENT POLICY IN MANAGING THE BINJAI TAVIP MARKET: CHALLENGES AND PROSPECTS - Nasti Hasyim Nasution; Abdi Sugiarto; Ruri Prihatini Lubis (Bulletin of Engineering Science, Technology and Industry, 2025)
This study aims to evaluate local government policies in managing Tavip Market in Binjai by highlighting the challenges faced and potential policy prospects for improving market management effectiveness. The evaluation was conducted based on regulatory aspects, infrastructure, and the roles of stakeholders involved. The results indicate that policy implementation still faces various obstacles, including a lack of outreach to traders, suboptimal supervision, and limited market infrastructure that hinders management effectiveness. Furthermore, coordination between local government, market managers, and traders still needs to be improved to create a more organized, safe, and comfortable market environment. Supervision conducted by the Binjai City Manpower, Industry, and Trade Office has been carried out in accordance with existing regulations, but has not been optimal in encouraging vendor compliance with the established rules. The disposition or attitude of policy implementers also influences implementation effectiveness, with commitment and a strong understanding of the implementers being key to successful market management. Stakeholder involvement, including vendors and the surrounding community, is also crucial in maintaining order and comfort in the market. To improve the effectiveness of the management of Binjai's Tavip Market, this study recommends strengthening regulations through the stricter implementation of Binjai Mayoral Regulation Number 35 of 2016, improving market infrastructure to make it more adequate, and increasing stakeholder participation in market management through a collaborative approach. Furthermore, policy dissemination to traders needs to be improved so they better understand and comply with applicable regulations. With more targeted policies, strong synergy between related parties, and adequate infrastructure support, it is hoped that Binjai's Tavip Market can develop into a modern, clean, and highly competitive traditional market, thereby improving the welfare of traders and providing broader benefits to the people of Binjai City.